REVIEW THE ASSESSMENT OF EFFECTS OF LOST TIME INJURIES IN AN INDUSTRIAL SYSTEM BY USING AN EXPLANATORY PROGRAM (Journal of Engineering, 2012)
Health and safety problem can be described by statistics it can only be understood by knowing and feeling the pain, suffering, and depression. Health and safety has a legal responsibility to protect it for everyone who can affect in the workplace. This includes manufacturers, suppliers, designers and controllers of work places and employees. Work injury is one of the major problems in manufacturing and production systems industries; it is reduced production efficiency and affects the cost. To gain flexibility from a traditional manufacturing system and production efficiency, this paper is about the application of estimating technology to preview and synthesis of Lost Time of Work Injuries in industry systems aims to provide a safe working environment for all employees to achieve safe workplaces, safe systems of work, and safety understanding within our workforce. Our industry oftenhas a poor record in dealing with modern and development techniques. Thus, as one of the targets, this leads to perform a helpful program plane to provide guidelines of management, employees to eliminate hazards, given the enormous cost of occupational personal damage in industry and to develop safe work methods work site. This work proposed a general methodology for constructing an explanatory software system to review and analysis workers injuries in a work site. The program language used is Axes, which suitable to shows categories of incidences and estimates costs to workers, employers and society of workplace injuries and work-related ill health. Data of the system was collected in the State Company for Woolen Industries in Al-Kadhumiaa in Iraq.The resulting is to provide a simple obvious outline system to evaluate lost time injury and the net-costs on safety interfering at the company level to reduce occupational morbidity and generating a helpful system to estimate of the total costs to employers and workers of workplace accidents and work-related ill health.